2010
DOI: 10.1186/1472-684x-9-5
|View full text |Cite
|
Sign up to set email alerts
|

The transition experience of rural older persons with advanced cancer and their families: a grounded theory study

Abstract: BackgroundTransitions often occur suddenly and can be traumatic to both patients with advanced disease and their families. The purpose of this study was to explore the transition experience of older rural persons with advanced cancer and their families from the perspective of palliative home care patients, bereaved family caregivers, and health care professionals. The specific aims were to: (1) describe the experience of significant transitions experienced by older rural persons who were receiving palliative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
1
22

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(157 citation statements)
references
References 19 publications
(30 reference statements)
2
132
1
22
Order By: Relevance
“…The studies in this review revealed that nurturing supportive networks and close-knit communities often exist within rural areas (Duggleby et al, 2010;Rogers-Clark, 2002). Alternatively, challenges related to lack of privacy, feelings of isolation, and difficulties finding the appropriate support or support groups at home were also identified (Gray et al, 2004;Rogers-Clark, 2002).…”
Section: Social Domainmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies in this review revealed that nurturing supportive networks and close-knit communities often exist within rural areas (Duggleby et al, 2010;Rogers-Clark, 2002). Alternatively, challenges related to lack of privacy, feelings of isolation, and difficulties finding the appropriate support or support groups at home were also identified (Gray et al, 2004;Rogers-Clark, 2002).…”
Section: Social Domainmentioning
confidence: 99%
“…The most noteworthy finding in the reviewed studies was that participants face challenges related to service provision in their rural communities. Of the 23 studies reviewed, 10 articles revealed service provision challenges such as lack of access to cancer information, limited access to professional or hospital assistance, and isolation from professional support or other supportive services were enduring challenges (Clavarino et al, 2002;Duggleby et al, 2010;Engleman, Perpich, Peterson, Hall, & Ellerbeck, 2005;Fitch et al, 2003;Gray, James, Manthorne, Gould, & Fitch, 2004;McConigley et al, 2011;McGrath, 2001;Rogers-Clark, 2002;Wilkes, White, & Riordan, 2000;Wilkes, White, Mohan, & Beale, 2006).…”
Section: Continued On Page 161…mentioning
confidence: 99%
See 2 more Smart Citations
“…Bien que la plupart des personnes choisissent consciemment d'habiter dans des régions rurales, les soins de santé dans ces régions constituent un important enjeu de santé publique. La documentation scientifique semble indiquer que les gens aiment la vie rurale pour différentes raisons, dont une communauté de soutien serrée, des expériences culturelles positives, un sentiment de paix ou d'harmonie et une autonomie accrue dans la vie quotidienne (Duggleby et al, 2010;Kuliq & Williams, 2012;RogersClark, 2002;Wilkes & White, 2005). Cependant, les personnes atteintes de cancer peuvent choisir de quitter les régions rurales afin d'habiter plus près des centres de soins médicaux spécia-lisés.…”
Section: Contexteunclassified